Arrays of ZnSe/MoSe2 Nanotubes with Electronic Modulation as Efficient Electrocatalysts for Hydrogen Evolution Reaction. Issue 23 (13th October 2017) - Wu, Meihui; Huang, Yanyan; Cheng, Xialan; Geng, Xiangshun; Tang, Qiong; You, Yu; Yu, Yongqiang; Zhou, Ru; Xu, Jun
Abstract: Few‐layered MoSe2 nanosheets have great promise as a low‐cost alternative to noble Pt‐based electrocatalysts for electrochemical hydrogen evolution reaction (HER). In this work, arrays of ZnSe/MoSe2 nanotubes on fluorine‐doped tin oxide (FTO) glass substrates are synthesized and employed as an efficient binder‐free HER electrocatalyst for the first time. The hybrid ZnSe/MoSe2 nanotubes have thicknesses of 3–20 nm. The growth of ZnSe layer is attributed to ion exchange with ZnO nanorods while the formation of MoSe2 layer is resulted from chemical bath deposition. Compared with the bare MoSe2 electrocatalyst, the hybrid ZnSe/MoSe2 nanotube electrocatalyst exhibits striking kinetic metrics with a small Tafel slope (73 mV per decade) and a low onset potential (68 mV). Beside benefits from the nanoarray structure as binder‐free electrode as well as interlayer expansion of layered MoSe2, electron transfer from n‐type ZnSe to MoSe2 induced by alignment of energy levels at heterointerface contributes to fast electron transport and active electrocatalytic behavior of MoSe2 at the electrocatalyst–electrolyte interface, which is responsible for the significant improvement in HER performance. This work opens up a new door for developing high‐performance HER electrocatalysts by designing semiconductor heterojunction. Abstract : Arrays of ZnSe/MoSe2 nanotubes grown on fluorine‐doped tin oxide glass substrates are synthesized and demonstrated as an efficient binder‐free electrocatalyst for enhanced hydrogen evolution reaction. Energy band alignment between ZnSe and MoSe2 facilitates electron injection into MoSe2 and promotes fast electron transfer at the MoSe2 –electrolyte interface for hydrogen evolution reaction.